Manajemen Kepemimpinan Kepala Sekolah dalam Meningkatkan Partisipasi Guru di SMP Negeri 3 Hamparan Perak - Hasbi, Mhm Fuad; Prasetia, Indra; Isman, Muhammad (UMSU, 2025)
The purpose of this study is to describe and analyse the principal's leadership management so as to create an increase in teacher participation at SMP Negeri 3 Hamparan Perak. This research uses descriptive qualitative method. The data sources were the principal, vice principal, teachers, and teachers. The results of the research are: (1) The principal's leadership management ability in planning to increase teacher participation has gone well according to teacher participation indicators, (2) The principal's leadership management ability in organising to increase teacher participation has gone well according to teacher participation indicators, (3) The principal's leadership management ability in controlling to increase teacher participation has gone well according to teacher participation indicators, (4). The principal's leadership management ability in involving teacher participation has gone well according to teacher participation indicators, and (5) The obstacle factors faced by the principal in increasing teacher participation at SMP Negeri 3 Hamparan Perak, namely: the existence of teachers who have low awareness of increasing teacher participation, there are still teachers who are less competent and there are still a lack of teachers as needed. From the overall leadership management of the principal, it can be stated that the principal of SMP Negeri 3 Hamparan Perak has carried out good leadership management.